2012
DOI: 10.1038/srep00482
|View full text |Cite
|
Sign up to set email alerts
|

Spatially non-uniform ground state and quantized vortices in a two-component Bose-Einstein condensate of magnons

Abstract: A gas of magnons in magnetic films differs from all other known systems demonstrating Bose-Einstein condensation (BEC), since it possesses two energetically degenerate lowest-energy quantum states with non-zero wave vectors ±kBEC. Therefore, BEC in this system results in a spontaneously formed two-component Bose-Einstein condensate described by a linear combination of two spatially non-uniform wave-functions ∝exp(±ikBECz), while condensates found in other physical systems are characterized by spatially uniform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
90
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(97 citation statements)
references
References 34 publications
5
90
2
Order By: Relevance
“…Such a phase separation can lead to the formation of "domains" of magnons with different density of magnons having opposite wave numbers, and, as a consequence, to the reduction of the per-particle energy. A strong phase separation of magnons in mBEC is not observed in our experiments with spatial resolution [33,34] , and the pronounced domains cannot be formed under a relatively low pumping rate used in our experiments.…”
Section: Discussionmentioning
confidence: 70%
“…Such a phase separation can lead to the formation of "domains" of magnons with different density of magnons having opposite wave numbers, and, as a consequence, to the reduction of the per-particle energy. A strong phase separation of magnons in mBEC is not observed in our experiments with spatial resolution [33,34] , and the pronounced domains cannot be formed under a relatively low pumping rate used in our experiments.…”
Section: Discussionmentioning
confidence: 70%
“…Kalinikos and Slavin 11 received a dispersion relation, in which the term 2πM (1 − e −kzd )/k z d replaces the magnetostatic contribution in our dispersion relation (22) …”
Section: Spin Waves In Films Boundary Conditionsmentioning
confidence: 99%
“…Malomed et al 21 solved numerically the GrossPitaevskii equation with added spin pumping and relaxation and found that sometimes asymmetric magnon distributions emerge, but only at asymmetric boundary conditions. Experimentally Nowik-Boltyk et al 22 revealed spatial periodic oscillations of magnon density, which are possible only if magnons condense in the both energy minima.…”
mentioning
confidence: 99%
“…It is also known that such dislocations strongly influence the magnetic dynamics in YIG. 28 Possible mechanisms of the defect-mediated symmetry breaking can include a growth-induced imbalance between clockwise and counter-clockwise screw dislocations in conjunction with a spin-orbit interaction.…”
Section: Fmr Measurementsmentioning
confidence: 99%